2020
DOI: 10.3390/polym12051126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of A Novel Smart Polymeric Nanodrug in the Treatment of Experimental Wounds in Rats

Abstract: High-quality and aesthetic wound healing, as well as effective medical support of this process, continue to be relevant. This study aims to evaluate the medical efficacy of a novel smart polymeric nanodrug (SPN) on the rate and mechanism of wound healing in experimental animals. The study was carried out in male Wistar rats (aged 8–9 months). In these animals, identical square wounds down to the fascia were made in non-sterile conditions on the back on both sides of the vertebra. SPN was used for the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…Thus, the effectiveness of the use of SPN and SPN + SC for the treatment of wounds has been determined. The results obtained are consistent with the opinion of earlier studies on the effective use of polymers [ 10 , 11 , 12 , 13 , 14 , 24 ] and molecules of cerium dioxide [ 20 , 21 , 22 , 23 , 24 , 25 ] for the treatment of wounds. In addition, our study confirms the results of other studies that the introduction of nanoparticles of certain substances radically changes the effectiveness of drugs, and this represents a quantum leap in providing safe and effective targeted drug delivery to the affected tissues [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the effectiveness of the use of SPN and SPN + SC for the treatment of wounds has been determined. The results obtained are consistent with the opinion of earlier studies on the effective use of polymers [ 10 , 11 , 12 , 13 , 14 , 24 ] and molecules of cerium dioxide [ 20 , 21 , 22 , 23 , 24 , 25 ] for the treatment of wounds. In addition, our study confirms the results of other studies that the introduction of nanoparticles of certain substances radically changes the effectiveness of drugs, and this represents a quantum leap in providing safe and effective targeted drug delivery to the affected tissues [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…As a result, the concentration of substances in the gel base of the matrix was (in mass percent): carboxymethyl cellulose—1.0; pectin—0.1; chitosan—0.01; agar—0.1; alginate—0.05; cerium oxide in the form of a colloidal sol of nanoparticles—0.0002. A preliminary analysis of the developed agent, as well as the results of experiments, demonstrating its safety and biocompatibility, were presented earlier [ 24 , 25 , 29 , 30 ]. SPN was applied topically once a day on day 0, 1, 3, 5, and 7 by applying it over the wound with a needle-free syringe and filling its volume using 1 mL per cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A culture of progenitor mesenchymal stem cells was prepared according to the technology described above. Then, the culture was added to our biological product based on natural and synthetic polymers 27 , 28 under the standard conditions. In total, 1 mL of the stem cell suspension was introduced drop by drop into 10 mL of gel in a bottle at room temperature and was stirred on a magnetic stirrer at a low speed for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Weaver and Stabler proposed a CeNPs-containing alginate hydrogel for cellular transplantation; this composite hydrogel provided cytoprotection for encapsulated beta cells from free radical attack without any signs of cytotoxicity, even up to 10 mM concentration [ 49 ]. Citrate-stabilized CeNPs integrated into a polysaccharide hydrogel matrix containing natural and synthetic polysaccharide polymers (pectin, alginate, chitosan, agar-agar, water-soluble cellulose derivatives) were used as the therapeutic agent for wound healing in vivo (male Wistar rats) [ 92 ]. The study showed that this type of dressing enhanced wound healing by inhibiting the inflammatory response and accelerating the development of fibroblasts, with an early onset of new collagen synthesis, which led to the formation of more tender postoperative scars.…”
Section: Ceria-containing Gel-like Polymeric Materialsmentioning
confidence: 99%